2023
DOI: 10.1186/s12905-023-02388-y
|View full text |Cite
|
Sign up to set email alerts
|

Proportion and associated factors of maternal complications of cesarean sections among mothers who deliver at Bahir Dar City Public Specialized Hospitals, Bahir Dar, Ethiopia

Abstract: Introduction Cesarean delivery carries both short term and long-term maternal complications. Eventhough it’s being a public burden, the proportion of complications and underlying risk factors are not studied well in our setup. This study aimed to assess the proportion and associated factors of complications of cesarean sections among mothers who delivered at Bahir Dar city public specialized hospitals, Bahir Dar, Ethiopia 2021. Methods A cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
1
2
Order By: Relevance
“…The most frequent indication on present study was previous CS for both elective and emergency CS, our study consistent with several studies and literature review [7][8][9][10]. On recent study in Ethiopia (2023) had reported that the intraoperative surgical complications was accounts 10.7% of overall caesarean delivery with documented complications were bleeding 3.6% (18), incision extension 1.4% (7) and adjacent internal organ injury 0.2% (1) [11]. Also, this study had reported that the rate of maternal complications were three times more frequent among emergency delivery on compare to elective delivery [11].…”
Section: Bowel Injury 0supporting
confidence: 88%
See 1 more Smart Citation
“…The most frequent indication on present study was previous CS for both elective and emergency CS, our study consistent with several studies and literature review [7][8][9][10]. On recent study in Ethiopia (2023) had reported that the intraoperative surgical complications was accounts 10.7% of overall caesarean delivery with documented complications were bleeding 3.6% (18), incision extension 1.4% (7) and adjacent internal organ injury 0.2% (1) [11]. Also, this study had reported that the rate of maternal complications were three times more frequent among emergency delivery on compare to elective delivery [11].…”
Section: Bowel Injury 0supporting
confidence: 88%
“…On recent study in Ethiopia (2023) had reported that the intraoperative surgical complications was accounts 10.7% of overall caesarean delivery with documented complications were bleeding 3.6% (18), incision extension 1.4% (7) and adjacent internal organ injury 0.2% (1) [11]. Also, this study had reported that the rate of maternal complications were three times more frequent among emergency delivery on compare to elective delivery [11]. On Al-Zirqi, et al study (2008) had revealed that rate of severe obstetrical haemorrhage linked significantly with emergency delivery as present study [12].…”
Section: Bowel Injury 0mentioning
confidence: 99%
“…However, this finding was relatively lower than findings in Arba-minch (38.2%) ( 19 ), Bahirdar (44.04%) ( 28 ) and Hawassa (56%) ( 29 ). The possible explanation might be due to the discrepancy in number of obstetrics emergency cases for hospitals.…”
Section: Discussioncontrasting
confidence: 65%
“…However, this finding was relatively lower than findings in Arba-minch (38.2%) (19), Bahirdar (44.04%) (28) Intraoperative maternal among mothers who underwent a caesarean section in Gebretsadik Shewa general hospital. Postoperative maternal complications among mothers who underwent a caesarean section in Gebretsadik Shewa general hospital.…”
Section: Discussioncontrasting
confidence: 54%